2012
DOI: 10.4055/cios.2012.4.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sigmoid Notch Involvement in the Intra-Articular Distal Radius Fractures: The Efficacy of Computed Tomography Compared with Plain X-ray

Abstract: BackgroundThe purpose of this study is to evaluate the efficacy of computed tomography (CT) scans compared with plain radiographs on detecting the involvement of the sigmoid notch.MethodsThis study involved 121 cases diagnosed as the intra-articular distal radius fracture and performed post-reduction CT scans. We determined the presence of the sigmoid notch involvement with both plain radiographs and CT scans and compared findings of plain radiographs with CT scans about the incidence and the pattern of injuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Multislice CT (MSCT) is superior to conventional radiography in sensitivity for fractures [1,2], assessment of intraarticular fractures [3,4], and in the accuracy of fracture measurements [5,6]. Zbijewski et al [7] identified three factors that limit a broader application of MSCT as an alternative to conventional x-ray imaging in musculoskeletal (MSK) imaging: MSCT imaging does not allow for weight-bearing examinations, applies more radiation dose, is more costly, and has larger spatial demands [7].…”
Section: Introductionmentioning
confidence: 99%
“…Multislice CT (MSCT) is superior to conventional radiography in sensitivity for fractures [1,2], assessment of intraarticular fractures [3,4], and in the accuracy of fracture measurements [5,6]. Zbijewski et al [7] identified three factors that limit a broader application of MSCT as an alternative to conventional x-ray imaging in musculoskeletal (MSK) imaging: MSCT imaging does not allow for weight-bearing examinations, applies more radiation dose, is more costly, and has larger spatial demands [7].…”
Section: Introductionmentioning
confidence: 99%
“…( 2001 ) and Heo et al. ( 2012 ) reported that sigmoid notch involvement is underestimated when using only CR. This feature is also seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the use of CT scans in all patients to detect dorsal lunate fractures may have overdiagnosed patients. 1,4,32 Fourth, all the measurements were performed by one investigator. Finally, our follow-up limits conclusions regarding osteoarthritic changes of the radiocarpal and DRU joint.…”
Section: Discussionmentioning
confidence: 99%